Meta-analysis comparing direct oral anticoagulants versus vitamin K antagonists in patients with left ventricular thrombus. - Kazuhiko Kido (Public Library of Science (PLoS), 2021)
Current American College of Cardiology/American Heart Association guidelines for stroke or ST-elevation myocardial infarction recommend the use of oral vitamin K antagonists (VKAs) as a first-line anticoagulant. Although several studies have compared the use of direct oral anticoagulants (DOACs) to VKAs for left ventricular thrombus (LVT) anticoagulation therapy, they are small scale and have produced conflicting results. Thus, this meta-analysis was performed to aggregate these studies to better compare the efficacy and safety of DOACs with VKAs in patients with LVT. Cochrane Library, Google Scholar, MEDLINE, and Web of Science database searches through January 10, 2021 were performed. Eight studies evaluating stroke or systemic embolism (SSE), six studies for LVT resolution, and five studies for bleeding were included. There were no statistically significant differences in SSE (OR 0.89; 95% CI 0.46, 1.71; p = 0.73; I2 = 45%) and LVT resolution (OR 1.13; 95% CI 0.75, 1.71; p = 0.56; I2 = 1%) between DOAC and VKA (reference group) therapy. DOAC use was significantly associated with lower bleeding event rates compared to VKA use (OR 0.61; 95% CI 0.40, 0.93; p = 0.02; I2 = 0%). DOACs may be feasible alternative anticoagulants to vitamin K antagonists for LV thrombus treatment. Randomized controlled trials directly comparing DOACs with VKAs are needed.